Children and Young Anxiety Scale- CYAS: Scale Development and Psychometric Properties in Brazilian Sample - Thiago Francisco Pereira Soares; Makilim Nunes Baptista (International Journal of Psychological Research, 2019)
The aim of the study was to search for evidence of validity based on the relationship with external variables, and incrementally for the Child-Youth Anxiety Scale (CYAS). The convenience sample consists of 500 children and adolescents aged 10 to 18 years. The correlation between the scores of the CYAS factors and the scores of the instruments of the other constructs ADHD (MTA-SNAP-IV), anxiety (OQPS), rumination (QRR) and mood states (BRUMS) was initially performed, finding medium and strong correlations, which shows a satisfactory linear relation between the constructs to attest validity based on the relation with external variables. Structural Equation Modeling (SEM) was also performed with total MTA-SNAP-IV and its factors as criterion. In the modeling, it was possible to observe that, when introduced in the models, the CYAS becomes the latent variable with the greatest contribution, decreasing and canceling the OQPS contribution. These results affirm incremental validity for the CYAS.